Resilience Strategies of Students in Highly Complex Educational Contexts: Opportunities for Inclusive Pedagogical Transformation - Santos-Villalba, María Jesús; Leiva-Olivencia, Juan José; González Sodis, José Luis; Alcalá-del-Olmo-Fernández, María José (Education Sciences, 2024)
The COVID-19 pandemic had various effects on the social, personal and educational spheres that made it necessary to rethink how to respond to new emerging needs. In Spain, a massive closure of schools occurred, which led to a transition from face-to-face teaching to emergency remote teaching. This led to the implementation of pedagogical measures to ensure continuity in the teaching process. The aim of this research is to explore the impact of the pandemic on the educational and personal trajectories of students from their own experiences of attending a poorly performing school in the province of Malaga (Spain). The methodology was qualitative, and the information was collected through a focus group. The most relevant results indicated that the students, in response to the pandemic situation, developed resilience strategies to cope with the lack of technological devices, connectivity problems, difficulties in managing their emotions and the absence of interactions with their peer groups. The main conclusions include the need to build resilient and inclusive educational spaces as key pillars for educational transformation.
Keywords: Educación - Aspectos sociales; COVID-19; Distance Education; Inclusive Education; Social Inequality